2020
DOI: 10.1177/0016986220969392
|View full text |Cite
|
Sign up to set email alerts
|

Social–Emotional Characteristics and Adjustment of Accelerated University Students: A Systematic Review

Abstract: Gifted students who experienced grade-based acceleration in primary or secondary education have to meet the challenges of adjusting to university at a younger age than students who did not accelerate. This systematic review critically evaluates the research on social–emotional characteristics and adjustment of these gifted accelerated university students. Based on a review of 22 studies, we may conclude that accelerated students did not differ very much in domains of social–emotional characteristics from their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
3
0
1
Order By: Relevance
“…It is worth mentioning that differentiated instruction is not usually practiced in Brazilian mainstream education. Concerning acceleration programs, although Brazilian legislation mandates that gifted children can accelerate to fulfill curriculum requirements in less time, and research results demonstrated the positive influence of acceleration on gifted students’ development, parents, educators, and school principals remain resistant to its implementation (Alencar et al, 2019; Schuur et al, 2021; Steenbergen-Hu & Moon, 2011). In Brazil, teachers’ knowledge about giftedness remains limited, and coverage of the topic is almost nonexistent in undergraduate education courses (Martins et al, 2018; Ramalho et al, 2014), which influences the way teachers respond to the needs of gifted students.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that differentiated instruction is not usually practiced in Brazilian mainstream education. Concerning acceleration programs, although Brazilian legislation mandates that gifted children can accelerate to fulfill curriculum requirements in less time, and research results demonstrated the positive influence of acceleration on gifted students’ development, parents, educators, and school principals remain resistant to its implementation (Alencar et al, 2019; Schuur et al, 2021; Steenbergen-Hu & Moon, 2011). In Brazil, teachers’ knowledge about giftedness remains limited, and coverage of the topic is almost nonexistent in undergraduate education courses (Martins et al, 2018; Ramalho et al, 2014), which influences the way teachers respond to the needs of gifted students.…”
Section: Discussionmentioning
confidence: 99%
“…Social adjustment measures to include a wide variety of characteristics such as social self-concept, social maturity, peer acceptance, friendships, engagement in organizations, and family relations. Accordingly, the social skills, participation in extracurricular activities, leadership positions held, self-concept scores, risk taking, independence, and creativity of the adolescents help to identify their adjustment pattern in the life 12 . Pre university College is one the most important foundation pillars on which the adolescent's personality develops.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the good life has been of concern among philosophers and psychologists since time immemorial. The literature is replete with conceptual and empirical studies on it, albeit being mooted with varied terms, such as "happiness," "social-emotional wellbeing," "life satisfaction," "quality of life," "meaning in life," and "spiritual intelligence" (Genç, 2021;Hassan, 2020;Sarifuddin et al, 2021;Schuur et al, 2020;Skrzypińska, 2021;Stammler & Toivanen, 2022). Similar terms also exist in other cultures and languages: these include the Japanese word ikigai, which means "a reason for being or something that make one's life worthwhile'; the Nguni Bantu term ubuntu, which means 'humanity' and is often understood as "the belief in a universal bond of sharing that connects all humanity"; and the Swedish word lagom, that implies "in moderation" (Abdul Razak, 2020, p. xiii-xiv).…”
Section: Introductionmentioning
confidence: 99%